The Effect of Concentration and Frequency of Application of Banan Weevil Solution Kepok on Red Chili - Oktavianus Lumban Tobing; Yanyan Mulyaningsih; Raden Danuningrat (Universitas Djuanda, 2021)
The purpose of the study is to determine the effect of concentration and frequency of application of banana weevil solution kepok against red chili plants is roofed with translucent ultraviolet plastic 70% which acts as a natural growth regulator. Research on the provision of banana weevil solution covered in 70% translucent ultraviolet plastic in open land has not been found before. The growing regulators from the gibberellin and cytokinin groups were able to boost the growth and yield of chili peppers. The method of using a random design of factorial groups, as the first factor is age consists of 9 levels, namely T1: age (14) HSPT, T2: age (14.21) HSPT, T3: age (14,21,28) HSPT, T4: age (14,21,28, 35) HSPT, T5 : age (14,21,28,35, 42) HSPT, T6: age (14,21,28,35,42,49) HSPT, T7: age (14,21,28,35,42,49,56) HSPT, T8: age (14,21,28,35,42,49,56,63) HSPT, and control (T0). The second factor is concentration consists of 3 levels, namely K1 (30%), K2 (45%), and K0 (0%). The results of the study obtained concentration of K1 (30%) with the amount of T6 administration is the best result in vegetative growth of the plant height change, the number of branches, and the width of the header, while the concentration of K1 (30%) give the best results on the length of the fruit, the dry weight of the fruit, and the diameter of the fruit from other treatments. Conclusion of the application of concentration and frequency of the sea of banana weevil kepok containing regulatory substances growing on red chili plants in the field covered with ultraviolet plastic roof significantly increases the growth and yield of red chili peppers.